Efektivitas Ekstrak Spirulina platensis sebagai Antiinflamasi terhadap Jumlah Neutrofil dan Makrofag pada Luka yang Diinfeksi Staphylococcus aureus pada Tikus Wistar - Misfa, Olvaria; Utami, Riski Dwi; Irenesia, Bimby; Marwan, Deinike Wanita (Universitas HKBP Nommensen, 2022)
ABSTRAK Latar belakang: Kandungan senyawa aktif dari Spirulina sp. memiliki aktivitas antiinflamasi dan antibakteri. Penggunaan senyawa tersebut berperan dalam proses inflamasi pada luka yang terinfeksi. Tujuan: Menganalisis efektifitas pemberian ekstrak Spirulina platensis terhadap jumlah neutrofil dan makrofag pada luka insisi tikus wistar yang diinfeksikan S. aureus. Metode: Penelitian ini menggunakan randomized post test only control group design. Dua puluh empat ekor tikus wistar jantan diinsisi kulitnya dan diinfeksikan S.aureus dibagi menjadi 4 kelompok, yaitu kelompok yang diberi ekstrak S.platensis dosis 500 mg/kgBB/hari, dosis 750 mg/kgBB/hari, kelompok kontrol negatif diberi larutan salin serta kelompok kontrol positif dengan pemberian amoksisilin 150 mg/kgBB peroral. Jumlah neutrofil dan makrofag dihitung pada pemeriksaan histopatologis dari jaringan luka pada hari ke-14 yang mencakup 5 lapang pandang. Analisis data dilakukan dengan uji one way ANOVA dan dilanjutkan dengan Post Hoc Test LSD. Hasil: Rerata jumlah neutrofil hari ke-14 pada kelompok dosis 500 mg/kgBB/hari, 750 mg/kgBB/hari, kontrol positif dan kontrol negatif adalah 17,83; 12,17; 5,17; dan 8,83 dengan p < 0,001. Jumlah makrofag hari ke-14 pada kelompok dosis 500 mg/kgBB/hari, 750 mg/kgBB/hari, kontrol positif dan kontrol negatif adalah 7,17; 10,83; 16,83; 15,83 dengan p < 0,002. Uji Post Hoc menemukan jumlah neutrofil pada kelompok dosis 500 mg/kgBB/hari secara signifikan lebih tinggi dibandingkan kelompok lainnya. Sementara, uji Post Hoc untuk jumlah makrofag menemukan perbedaan signifikan hanya pada kelompok dosis 500 mg/kgBB/hari terhadap kelompok kontrol positif dan kontrol negatif. Simpulan: Pemberian ekstrak Spirulina platensis dosis 500mg/kgBB/hari secara signifikan meningkatan jumlah neutrofil dan menurunkan jumlah makrofag pada luka insisi tikus wistar yang diinfeksikan Staphylococcus aureus . Kata kunci: luka, makrofag, neutrofil, Spirulina platensis ABSTRACT Background: The active compound of Spirulina sp. has anti-inflammatory and antibacterial property. The use of these contents plays a role in the inflammatory process in infected wounds. Objective: To analyse the effectiveness of Spirulina platensis extract on the number of neutrophils and macrophages in the incision wound of Wistar rats infected by S. aureus. Methods: This study used a randomized posttest-only control group design. Twenty-four male Wistar rats had their skin incised and infected with S. aureus were divided into 4 groups. The group was given with the extract of S. platensis at a dose of 500 mg/kgBW/day (1), a dose of 750 mg/kgBW/day (2), the negative control group was given saline solution(3), and the positive control group was given amoxicillin 150 mg/kg body weight orally (4). The number of neutrophils and macrophages was counted on histopathological examination of the wound tissue on day 14 which included 5 visual fields. Data analysis was carried out by one way ANOVA test and followed by LSD Post Hoc Test . This study used a randomized posttest-only control group design. Twenty-four male wistar rats were divided into 4 groups, the groups were given S. platensis extract 500 mg/kgBW/day and 750 mg/kgBW/day, the positive control group was given amoxicillin 150 mg/kgBW orally and the negative control group was given saline solution. The skin of the mice was incised and infected with S. aureus. Histopathological examination of wound tissue was performed on day 14 to assess the number of neutrophils and macrophages. Data analysis was carried out with the oneway ANOVA test. Results: The mean numbers of neutrophils on the 14th day in the group of a dose of 500 mg/kgBW/day, 750 mg/kgBW/day, positive control, and negative control were 17.83; 12.17; 5.17; and 8.83 with p < 0.001, respectively. The numbers of macrophages on the 14th day in the group of a dose of 500 mg/kgBW/day, 750 mg/kgBW/day, positive control, and negative control were 7.17; 10.83; 16.83; 15.83 with p < 0.002, respectively. The Post Hoc test exhibited that the neutrophil count in the group of 500 mg/kgBW/day was significantly higher than the other groups. Meanwhile, the Post Hoc test for the number of macrophages found a significant difference, only in the group of a dose of 500 mg/kgBW/day against the positive and negative control groups. Conclusion: There was a significant decrease in the number of macrophages in the group of wistar rats that were incised and infected with Staphylococcus aureus and given Spirulina platensis extract at a dose of 500mg/kgBW/day. Keywords: wound, macrophages, neutrophils, Spirulina platensis